Bertrand-Edgeworth markets with increasing marginal costs and voluntary trading: Experimental evidence - Martin Jacobs; Till Requate (Kiel University, Department of Economics, 2016)
Price competition with increasing marginal costs, though relevant for many markets, appears as an under-researched field in the experimental oligopoly literature. We provide results from an experiment that varies the number of firms as well as the demand rationing and matching schemes in Bertrand-Edgeworth markets with increasing marginal costs and voluntary trading. We find that prices and profits are substantially higher in duopoly than in triopoly and with proportional compared to efficient demand rationing. The matching rule has little effect on prices and profits. Nash equilibrium predictions do not capture observed behavior. Neither the mixed-strategy Nash equilibria of the underlying one-shot game nor, for the fixed matching condition, the symmetric stationary outcome pure-strategy Nash equilibria of the infinitely repeated game are supported by the data. In contrast to results from related experiments, behavior is largely more competitive than predicted by Nash equilibrium theory. Individual pricing decisions can predominantly be explained by either myopic best responses (Edgeworth cycles) or simple imitative behavior, where the complexity of the decision situation plays a crucial role in which behavioral pattern applies.
Keywords: C72; C90; D43; L13; 330; Bertrand-Edgeworth; demand rationing; increasing marginal costs; Edgeworth cycles; oligopoly; laboratory experiment